Biological larviciding against malaria vector mosquitoes with Bacillus thuringiensis israelensis (Bti) – Long term observations and assessment of repeatability during an additional intervention year of a large-scale field trial in rural Burkina Faso. Issue 1 (31st December 2020) - Dambach, Peter; Winkler, Volker; Bärnighausen, Till; Traoré, Issouf; Ouedraogo, Saidou; Sié, Ali; Sauerborn, Rainer; Becker, Norbert; Louis, Valérie R.
ABSTRACT: The first line of malaria vector control to date mainly relies on the use of long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS). For integrated vector management, targeting the vector larvae with biological larvicides such as Bacillus thuringiensis israelensis ( Bti ) can be an effective additional mainstay. This study presents data from the second intervention year of a large-scale trial on biological larviciding with Bti that was carried out in 127 rural villages and a semi-urban town in Burkina Faso. Here we present the reductions in malaria mosquitoes that were achieved by continuing the initial interventions for an additional year, important to assess sustainability and repeatability of the results from the first intervention year. Larviciding was performed applying two different larviciding choices ((a) treatment of all environmental breeding sites, and (b) selective treatment of those that were most productive for Anopheles larvae indicated by remote sensing based risk maps). Adult Anopheles spp. mosquito abundance was reduced by 77.4% (full treatment) and 63.5% (guided treatment) compared to the baseline year. The results showed that malaria vector abundance can be dramatically reduced using biological larviciding and that this effect can be achieved and maintained over several consecutive transmission seasons.